Mobile shopping continuance intentions of expats in China: influence of structural assurance and the stay duration. (15th July 2022) - Hanif, Muhammad Shehzad; Yunfei, Shao; Hanif, Muhammad Imran; Afzal, Farman
Mobile shopping continuance intentions tend to globally vary due to several factors exhibiting positive and negative influence. The majority of studies in the past assumed the adoption behaviours of local and expat communities to be the same towards mobile shopping. By integrating core tenets of the UTAUT2 model with the constructs of perceived risk, trust and structural assurance, this study aims to test the applicability of the model for a distinctive sample of expat students based in China using the structural equation modelling (SEM) technique. Results demonstrate the noticeable effects of perceived risk and trust whereas the vital counterbalancing influence is provided through moderating roles of structural assurance and the duration of stay in a foreign country. This study contributes to the technology adoption theory by analysing the post-adoption phase from the viewpoint of an expatriate consumer in a foreign country. Implications for both theory and practice are furnished followed by conclusion and research limitations.